Geochemical characteristics of abiogenic gas and its percentage in Xujiaweizi Fault Depression, Songliao Basin, NE China - Ni Yunyan; Dai Jinxing; Zhou Qinghua; Luo Xia; Hu Anping; Yang Chun (Petroleum Exploration and Development, 2009)
Gases with different origins occur in the Xujiaweizi Fault Depression. Among them, the abiogenic gases have a typical carbon isotopic reversal trend (δ13C1>δ13C2>δ13C3>δ13C4), the carbon isotope of methane greater than −30.0%, and the R/Ra greater than 0.5. According to the simulative calculation with two-source mixing (mixture of abiogenic gas and thermogenic gas), when the end composition of abiogenic gas being mixed with coal-derived gas or oil-derived gas, it will require an amount of abiogenic gas more than 80% to obtain the carbon isotopic reversal trend, which results in much heavier carbon isotope values of the mixed methane than the peak carbon isotope values of the abiogenic methane in the Xujiaweizi Fault Depression. Thus, it is argued that the abiogenic gases in the Xujiaweizi Fault Depression cannot simply be a result of two-source mixing. The mixing of coal-derived and oil-derived gases cannot lead to the carbon isotopic reversal trend, which provides further evidence for the abiogenic origin of the deep-layer gas. Key words: abiogenic origin, alkane gas, carbon isotopic reversal trend, Xujiaweizi Fault Depression, Songliao Basin